PRAKTIK OPEN GOVERNMENT MELALUI PARTISIPASI PUBLIK DI KABUPATEN BOJONEGORO DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS (Studi Kasus Dialog Publik Jumat di Kabupaten Bojonegoro) - Berlian Tyasotyaningarum (Universitas Kadiri, 2019)
AbstractPublic participation through the Friday Public Dialogue in Bojonegoro district is a form of open government practice in realizing transparency and accountability. Through these public participation development innovations, Bojonegoro district has gained achievements as a pilot project for open government in the world. This research uses qualitative research techniques with descriptive methods. This study aims to identify how open government practices through public participation can achieve transparency and accountability in the Bojonegoro district. The results of the study show that open government through public dialogue can achieve transparency in the form of delivery of information related to the socialization of government programs, finance, and public service delivery. Meanwhile, accountability is realized through public dialogue related to government performance and public services. Public dialogue has a role in realizing transparency and accountability practices in the Bojonegoro district, namely: increasing public trust, establishing community legitimacy, and improving decision-making. Lessons learned from public participation innovation through public dialogue in Bojonegoro district are the importance of direct communication between public officials and the community, the importance of the role of leaders as trainers, and public participation to ensure that the government is always connected to its people. Keywords: open government; public participation; transparency.AbstrakPartisipasi publik melalui Dialog Publik Jumat di kabupaten Bojonegoro merupakan salah satu wujud praktik open government dalam mewujudkan transparansi dan akuntabilitas. Melalui inovasi pembangunan partisipasi publik tersebut, kabupaten Bojonegoro telah mendapatkan prestasi sebagai proyek percontohan open government di dunia. Penelitian ini menggunakan teknik penelitian kualitatif dengan metode deskriptif. Studi ini bertujuan untuk mengidentifikasi bagaimana praktik open government melalui partisipasi publik dapat mewujudkan transparansi dan akuntabilitas di kabupaten Bojonegoro. Hasil studi menunjukkan bahwa open government melalui dialog publik dapat mewujudkan transparansi berupa: penyampaian informasi terkait sosialisasi program-program pemerintah, finansial dan penyelenggaraan pelayanan publik. Sedangkan akuntabilitas yang terwujud melalui dialog publik terkait kinerja pemerintah dan pelayanan publik. Dialog publik memiliki peran dalam mewujudkan praktik transparansi dan akuntabilitas di kabupaten Bojonegoro, yaitu : meningkatkan kepercayaan publik, membentuk legitimasi masyarakat serta memperbaiki pengambilan keputusan. Pembelajaran dari inovasi partisipasi publik melalui dialog publik di kabupaten Bojonegoro adalah: pentingnya komunikasi langsung antara pejabat publik dan masyarakat, pentingnya peran pemimpin sebagai pelatih, dan partisipasi publik memastikan bahwa pemerintah selalu terhubung dengan masyarakatnya.Kata Kunci: open government; partisispasi publik; transparansi.